Manajemen Perubahan untuk Mantan Karyawan: Evaluasi dan Penelitian atas Banyaknya Kegagalan dan Kendala dalam Menjalankan Bisnis Bagi Pemula: Episode 1. Bisnis Adalah Pelayanan dan Solusi Bagi Pelanggan (Konsep Pelayanan Pelanggan) - Puruhita, Prima (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The most certain thing to happen is change. The passage of time shows the certainty of this change itself, as we have understood that periods of time change episodes need to be addressed properly so that the changes that occur have a beneficial impact. Change always brings uncertainty, but always has patterns that can be learned to reduce the risk of uncertainty itself. For example, during the last pandemic in 2020 - 2022 there were many changes in people's activity patterns which greatly affected work patterns including the emergence of the term